Using oral feedback to help students in learn English - Nurasid, Eka Priminatha (Journal of English Teaching, Literature, and Applied Linguistics, 2019)
English is an international language, so its must for us to learning english. Feedback is a part in teaching process, most of teacher use feedback in teaching process, in the process of feedback, teacher can know how the students grow, respond to stress and challenge, and etc. There are 2 kinds of feedback. Written feedback and oral feedback. In this context the writer focus on oral feedback to help students learn english. There is the benefit of oral feedback based on findings which can help student learn englishthat positive feedback, however, can increase the likelihood that students will return to or persist in activity and self-report and higher interest in the activity. It have similiar thing with the third point, when you give a positive feedback the student will return and addiction with your feedback. And make the students more active in the class.